ISLAMIC RELIGIOUS EDUCATION AND THE FORMATION OF STUDENTS' MORAL CHARACTER - Ahmad Fauzi; Nur Aisyah Rahman (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2024)
This paper aims to determine whether Islamic religious education influences the formation of students' morals. This study uses a qualitative approach that is library research in nature. The data analysis method used is a descriptive analysis method carried out through the process of explaining and describing the influence of Islamic religious education in the formation of students' morals clearly, objectively and critically. The conclusion of this study is that Islamic religious education influences the formation of students' morals. This is based on the fact that Islamic religious education functions to provide and accommodate education about faith and morals as the main fundamental things in the formation of good morals or morals. The influence of Islamic religious education in the formation of students' morals is seen in the material delivered in the form of religion obtained from faith, laws in daily worship obtained from fiqh, guidelines for behavior obtained from moral education, life examples obtained from the history of previous peoples and life guidelines obtained from the Qur'an as the holy book of Muslims and As-Sunnah as well as through examples exemplified by teachers in everyday life.